Students’ Perceptions on Using Wattpad as Media in Extensive Reading - Nasution, Ayau Ummad (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This research aims to investigate students' opinions on extensive reading using the Wattpad platform and its advantages in enhancing English language proficiency. The study employed descriptive qualitative writing methods and conducted in-depth interviews with two undergraduate English education majors from a North Sumatra state university. These participants were purposively selected due to their substantial engagement in Wattpad's extensive reading for over three years. Data collected from the interviews were analysed to answer the research question. The findings demonstrate that extensive reading on Wattpad positively impacts students' language proficiency and supports better language memorization. In conclusion, this study sheds light on the benefits of online platforms like Wattpad in facilitating in-depth reading experiences for language learners.